Atrial and ventricular function after cardioversion of atrial fibrillation. Issue 3 (September 1995) - Xiong, C.; Sonnhag, C.; Nylander, E.; Wranne, B.
Abstract : OBJECTIVE–Previous studies on atrial recovery after cardioversion of atrial fibrillation have not taken into account new knowledge about the pathophysiology of transmitral and transtricuspid flow velocity patterns. It is possible to shed further light on this problem if atrioventricular inflow velocity, venous filling pattern, and atrioventricular annulus motion are recorded and interpreted together. DESIGN–Prospective examinations of mitral and tricuspid transvalvar flow velocities, superior caval and pulmonary venous filling, and mitral and tricuspid annulus motion were recorded using Doppler echocardiography. Examinations were performed before and 24 hours, 1 month, and 20 months after cardioversion. SETTING–Tertiary referral centre for cardiac disease with facilities for invasive and non-invasive investigation. PATIENTS–16 patients undergoing cardioversion of atrial fibrillation in whom sinus rhythm had persisted for 24 hours or more. RESULTS–Before conversion there was no identifiable A wave in transvalvar flow recordings. The total motion of the tricuspid and mitral annulus was subnormal and there was no identifiable atrial component. Venous flow patterns in general showed a low systolic velocity. After conversion, A waves and atrial components were seen in all patients and increased significantly (P < 0.01) with time. There was a similar time course for the amplitude of annulus atrial components, an increased systolic component of venous inflow, an increased A wave velocity, and a decreased E/A ratio of the transvalvar velocity curves. The ventricular component of annulus motion was unchanged. Changes in general occurred earlier on the right side than the left. CONCLUSIONS–This study indicates that, in addition to the previously known electromechanical dissociation of atrial recovery that exists after cardioversion of atrial fibrillation, there may also be a transient deterioration of ventricular function modulating the transvalvar inflow velocity recordings. Function on the right side generally becomes normal earlier than on the left. Integration of information from transvalvar inflow curves, annulus motion, and venous filling patterns gives additional insight into cardiac function.